Postbuckling behavior and imperfection sensitivity of elastic–plastic periodic plate-lattice materials. (January 2022) - Derveni, Fani; Gross, Andrew J.; Peterman, Kara D.; Gerasimidis, Simos
Abstract: Advances in additive manufacturing have enabled a new generation of materials with advantageous properties inherent to their architecture. Recently, architected materials with periodic arrangements of plates, called plate-lattice materials, have been developed to reach theoretical least upper bounds for stiffness and strength of isotropic materials. This work investigates the buckling behavior of several plate-lattice architectures with relative densities between 0.5% to 25% when subjected to uniaxial compression. Finite element unit cell models with shell elements and periodic boundary conditions are used to simulate the buckling and post-buckling behavior of plate-lattices made from an elastic-perfectly plastic parent material. Five plate-lattice architectures with cubic symmetry are investigated — three anisotropic architectures (simple cubic, body-centered cubic, face-centered cubic) and two isotropic architectures (simple cubic and body-centered cubic combination, simple cubic and face-centered cubic combination). Geometric imperfections of varying amplitude are applied to determine the imperfection sensitivity of these plate-lattice materials, and to calculate their buckling knockdown factors. Consistent with the behavior of the elastic–plastic plate building blocks that comprise the lattice, this investigation reveals that plate-lattice materials are generally imperfection insensitive when their constituent plates become thinner and first bifurcation occurs in the elastic range away from the yield stress. When this occurs, the initial post-buckling behavior is stable and the ultimate strength can be many times higher than the initial buckling stress.